Thermal traits for reproduction and recruitment differ between Arctic and Atlantic kelp Laminaria digitata - Martins, Neusa (2020)
The plasticity of different kelp populations to heat stress has seldom been investigated excluding environmental effects due to thermal histories, by raising a generation under common garden conditions. Comparisons of populations in the absence of environmental effects allow unbiased quantification of the meta-population adaptive potential and resolution of population-specific differentiation. Following this approach, we tested the hypothesis that genetically distinct arctic and temperate kelp exhibit different thermal phenotypes, by comparing the capacity of their microscopic life stages to recover from elevated temperatures. Gametophytes of Laminaria digitata (Arctic and North Sea) grown at 15°C for 3 years were subjected to common garden conditions with static or dynamic (i.e., gradual) thermal treatments ranging between 15 and 25°C and also to darkness. Gametophyte growth and survival during thermal stress conditions, and subsequent sporophyte recruitment at two recovery temperatures (5 and 15°C), were investigated. Population-specific responses were apparent; North Sea gametophytes exhibited higher growth rates and greater sporophyte recruitment than those from the Arctic when recovering from high temperatures, revealing differential thermal adaptation. All gametophytes performed poorly after recovery from a static 8-day exposure at 22.5°C compared to the response under a dynamic thermal treatment with a peak temperature of 25°C, demonstrating the importance of gradual warming and/or acclimation time in modifying thermal limits. Recovery temperature markedly affected the capacity of gametophytes to reproduce following high temperatures, regardless of the population. Recovery at 5°C resulted in higher sporophyte production following a 15°C and 20°C static exposure, whereas recovery at 15°C was better for gametophyte exposures to static 22.5°C or dynamic heat stress to 25°C. The subtle performance differences between populations originating from sites with contrasting local in situ temperatures support our hypothesis that their thermal plasticity has diverged over evolutionary time scales.